2022
DOI: 10.3389/fmicb.2022.1048648
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic differences in granulomas of Mycobacterium bovis bacille Calmette Guérin (BCG) vaccinated and non-vaccinated cattle with bovine tuberculosis

Abstract: Mycobacterium bovis (M. bovis) is the zoonotic bacterium responsible for bovine tuberculosis. An attenuated form of M. bovis, Bacillus Calmette-Guerin (BCG), is a modified live vaccine known to provide variable protection in cattle and other species. Protection for this vaccine is defined as a reduction in disease severity rather than prevention of infection and is determined by evaluation of the characteristic lesion of tuberculosis: the granuloma. Despite its recognized ability to decrease disease severity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Granuloma formation was not examined in the present study. Studies in cattle have shown granulomas do develop in lungs following experimental infection (50, 51). It was inferred from the study in mice and results from the study with Map that the BCG rel deletion mutant was cleared.…”
Section: Discussionmentioning
confidence: 99%
“…Granuloma formation was not examined in the present study. Studies in cattle have shown granulomas do develop in lungs following experimental infection (50, 51). It was inferred from the study in mice and results from the study with Map that the BCG rel deletion mutant was cleared.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies that have looked at the cellular composition of bovine granulomas experimentally infected with M. bovis. Using techniques such as IHC and in-situ hybridisation (ISH) it has allowed us to characterise, visualise and locate different cell types within the granuloma (5,7,70,(97)(98)(99). CD68 is commonly used to identify macrophages, epithelial cells and MNGCs to help differentiate the different stages of granuloma development (70).…”
Section: Rabbitsmentioning
confidence: 99%
“…The BCG vaccine has also been studied as a tool for controlling bovine tuberculosis (bTB) (4). While the vaccine is not highly effective in preventing M. bovis infection in cattle, it can provide protection against severe forms of the disease, reducing visible lesions, histopathological changes and the spread of infection (5,6).…”
Section: Open Access Edited Bymentioning
confidence: 99%